Comparative Study of Red-Picked and Random-Picked Robusta Coffee Farming Businesses among Small Farmers in Rejang Lebong, Bengkulu. - Oktoyoki, Hefri; Siswahyono, Siswahyono (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
This study compares the red cherry coffee harvesting method and the mixed-maturity coffee harvesting method in Suban Ayam Village, Rejang Lebong Regency, with an emphasis on farm income. The maturity of coffee cherries at harvest, particularly in the form of red cherry picking or various other stages of ripeness, results in coffee with different characteristics. The research aims to analyze the economic and cultural differences between these coffee harvesting methods. Primary data were collected through observations and direct interviews with farmers using questionnaires. Data analysis involved evaluating production costs, revenue and income, and R/C ratios, as well as comparing profits and expenses. The results show significant differences in production costs between red cherry coffee and mixed-maturity coffee, with red cherry coffee having lower production costs. The revenue from red cherry coffee was also higher per unit area per year, resulting in higher net income. Both methods have an R/C ratio greater than 1, indicating that both are feasible and profitable, but the R/C ratio for red cherry coffee (8.70) is higher, demonstrating its economic superiority. With the same land area and planting area, red cherry coffee has an R/C ratio of 7.6, indicating higher efficiency in generating greater income. These findings reflect the advantage for coffee farmers in Suban Ayam Village in using the red cherry coffee harvesting method. In conclusion, the red cherry harvesting method is more profitable in terms of income and economic efficiency compared to the mixed-maturity method. These results reflect the preference of coffee farmers in Suban Ayam Village for the red cherry method, which is more financially advantageous.